Life after death : approaches to a cultural and social history during the 1940s and 1950s - Bessel, Richard; Schumann, Dirk (Publications of the German Historical Institute., 2003)
This collection of essays offers a novel approach to the cultural and social history of Europe after the Second World War. In a shift of perspective, it does not conceive of the impressive economic and political stability of the postwar era as a quasi-natural return to previous patterns of societal development but approaches it as an attempt to establish 'normality' upon the lingering memories of experiencing violence on a hitherto unprecedented scale. It views the relationship of the violence of the 1940s to the apparent 'normality' and stability of the 1950s as a key to understanding the history of post-war Europe. While the history of post-war Germany naturally looms large in this collection, the essays deal with countries across Western and Central Europe, offer comparative perspectives on their subjects, and draw upon a wide range of primary and secondary source material.